Unveiling linguistic dynamic: exploring the Pahang dialect and its historical significance - Muhammad Norsyafiq Zaidi,; Rahim Aman,; Shahidi A.H.,; Nurul Shuhada Shafie, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Since 1912, the investigation of the Pahang dialect has intrigued scholars, and its significance has gained prominence in recent times. Previous research has primarily focused on linguistics, employing various approaches within this domain. This systematic literature review aims to provide a comprehensive understanding of the ongoing developments in the dialectal study in Pahang, Malaysia. By collecting, scanning, reviewing, and synthesizing information on this location-focused topic, we employ the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart and methodology. Our qualitative literature review included the analysis of sixteen (16) eligible full texts, resulting in the identification of three (3) key themes. Our findings emphasize the importance of expanding phonological and historical linguistic research along the Pahang River, shedding light on the linguistic aspects of human migration waves. A deeper exploration of phonological patterns and historical linguistic dynamics within the region will provide a more comprehensive understanding of migration patterns. Consequently, further research is imperative to illuminate the intricate relationship between language, migration, and the Pahang River region.